The divided earth - Hicks, Faith Erin (Hicks, Faith Erin. Nameless city (Series), 2018)
The Nameless City--held by the rogue Dao prince Erzi--is under siege by a coalition of Dao and Yisun forces who are determined to end the war once and for all... Rat and Kai must infiltrate Erzi's palace and steal back the ancient and deadly formula for napatha--the ancient weapon of mass destruction Erzi has unearthed--before he can use it to destroy everything they hold dear!"-- Back cover.